IMPLIKASI YURIDIS PUTUSAN MAHKAMAH KONSTITUSI NOMOR : 125/PHPU.D-XI/2013 TENTANG PERSELISIHAN HASIL PEMILIHAN UMUM KEPALA DAERAH KABUPATEN KERINCI TERHADAP PERKEMBANGAN DEMOKRASI - Johani Wilmen; Philips Adrianus Kana (UNES Journal of Swara Justisia, 2017)
The practice of the implementation of the Regional Head Election is always accompanied by disputes and conflicts. Through UU No. 12 Tahun 2008 on Amendment to UU No. 32 Tahun 2004 on Regional Government, the dispute over the General Election of Regional Head has been transferred from the Supreme Court to the Constitutional Court. The locus dispute settlement dispute is regulated in Article 236 C of UU No. 12 Year 2008. The change of dispute resolution to the Constitutional Court brings new hope because the settlement by the Constitutional Court is relatively not cause a significant conflict, so that democracy goes well. This is proven one of them is the settlement of disputes result of General Election of Head of Kerinci Regency by Constitutional Court with Decision No 125/PHPU.D-XI/2013. With the result of the decision of the Constitutional Court it can be ascertained that about the certainty of the elected Regent and Vice Regent Kerinci candidate who will lead Kerinci 5 years ahead. This research is normative research, that is studying result of Constitutional Court Decision No. 125/ PHPU.D-XI / 2013 about Dispute of Result of General Election of Region Head of Kerinci Regency.